Where are the "People Like me"?: A Collaborative Autoethnography of Transnational Lives and Teacher Education in the U.S. Issue 3 (3rd July 2018) - Vellanki, Vivek; Prince, Sharon Pavitha
ABSTRACT: Global multicultural teacher education courses and programs have made claims to offer Prospective Teachers (PSTs) a global understanding of diversity and multiculturalism. However, there is very little research that has examined the classroom experiences of PSTs and teacher educators. Drawing on a collaborative autoethnography, this article explores the ways our transnational identities shaped our experiences (as a PST and a teacher educator) in a global teacher education course focused on diversity and multiculturalism. We were guided by the following research question: How do we, as South Asian transnational migrants, experience the curriculum of a global multicultural education course in the United States? We found that the curricular nationalism within multicultural education courses often negates any critical engagement with the influence of transnationalism on immigrants and their educational experiences. Transnational migrants are expected to translate their experiences, cultural practices, and life ways to fit into the container of the U.S. nation-state. Furthermore, there was a visible absence of narratives and research about transnational lives and identities in the course curriculum. As teacher education programs prepare PSTs to enter classrooms with growing immigrant populations, it is important that we attend to this glaring gap in both practice and research.